LATE PLEISTOCENE TO HOLOCENE ENVIRONMENTAL CHANGES FROM δ 13C DETERMINATIONS IN SOILS AT TEOTIHUACAN, MEXICO - Baturina E.L.; Puente P.M.; Alvarado E.C.; Sedov S.; Gómez E.V.; Rebolledo E.S.; Báez H.V.C. (My University, 2006)
Stable carbon isotopic signature (δ13C) of soil organic matter (SOM) is used as a high-spatial resolution tool to infer environmental changes during late Pleistocene to Present in the Teotihuacan valley, Mexico. Interpretation was based on climatic preferences of C3, CAM and C4 plant groups. δ13C values of modern plant types are clearly distinguished. C3 plants display values around -27‰, while C4 and CAM plants have values around - 13‰. Data from soil profiles range from -25.7 to -15.5‰. Cerro Gordo site δ13C varyies around -20‰, indicating long-term, time-stable co-existence between C3 and C4 or CAM plants. The more depleted signatures (-23 ± 2 ‰) are, dominated by carbon from C3 vegetation of late Pleistocene swamp paleosols in the Tepexpan profile of the Lake Texcoco. Younger paleosols from lower valley sites, have less depleted values (-17 ± 1)‰, dominated by C4 and CAM carbon. Late Holocene and modern soils present slightly more negative values (1-2‰) with respect to δ13C of underlying soils. Our results show 1) an increase of 10-70 % depending on the site, during the transition from the late Pleistocene to early Holocene, and 2) a dominance of C4 vegetation, up to 84%, in valley environment during the middle Holocene. These data support a climatic change from cold and wet conditions in the Last Glacial Maximum and late Pleistocene, to warm and dry conditions in middle Holocene. A slight rise in moisture availability during late Holocene is inferred based on the 4-10% increase in C3 plant carbon in soils from the valley. Conditions remained generally warm and dry, much as they are at present, favouring the development of agriculture in the valley. Our interpretation agrees with results of paleoenvironmental studies at Texcoco Lake based on diatom and pollen analyses in lake.
Keywords: ARCHEOLOGICAL RECORDS; CARBON STABLE ISOTOPE; CENTRAL MEXICO; PALEOSOLS; QUATERNARY CLIMATIC CHANGES; TEOTIHUACAN; Holocene; Pleistocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен